Extinct Australian birds: numbers, characteristics, lessons and prospects - Woinarski, John C.Z.; Legge, Sarah M.; Garnett, Stephen T. (Emu, 2024)
Since European colonisation of Australia in 1788, nine Australian bird species (1.2% of the Australian total) have become extinct, along with 22 subspecies (of 16 species). Consistent with global patterns, Australia’s island endemic birds have been particularly susceptible, comprising eight of the nine species’ extinctions (38% of the bird species endemic to islands smaller than Tasmania), and 13 of the 22 subspecies’ extinctions. The extinction of only one bird species (Paradise Parrot Psephotellus pulcherrimus) from the Australian mainland contrasts with the far higher rate of extinctions of Australian mammals (27 of 312 species that occurred on the Australian mainland), and is comparable with the rate of extinctions of birds on the mainland of other continents over this period. Extinctions of Australian birds were caused mainly by introduced predators (especially for island taxa), habitat degradation, and hunting (for some island taxa). The timing of some extinctions is uncertain, but the first bird extinction subsequent to European colonisation was the loss of the flightless White Gallinule Porphyrio albus from Lord Howe Island over the period 1788–1790. Extinctions have occurred in most decades since then, with the most recent being for Norfolk Island’s White-chested White-eye Zosterops albogularis in the decade 2000–2009. Environmental legislation, an extensive conservation reserve system, and dedicated conservation management efforts have prevented some extinctions. However, local extirpations continue, many threatened species continue to decline and, without an increase in conservation efforts, the rate of extinctions is likely to increase, mainly due to the direct and compounding impacts of climate change. Extinctions of Australian birds have occurred in most decades since European colonisation of Australia. Island bird taxa have proven particularly susceptible, and many of the most imperilled birds are island endemics. Conservation management actions and policies have prevented (and continue to do so) some otherwise probable extinctions. The direct and indirect impacts of climate change will increase the likelihood of extinction for many bird taxa. There is uncertainty about the persistence or extinction of some bird taxa, and these are priorities for surveys and, if found, urgent management interventions.